Specific jurisdiction of commercial courts comparative study - Gheni Kadhim , Basim; Auda Ghanim , Prof.Dr.Yousif (Basra studies journal, 2022)
The development of commercial and economic activity in Iraq after 2003 was accompanied by the emergence of the need for a specialized commercial judiciary that provides a safe environment to attract and encourage investment. Judicial specialization is not achieved unless it accompanied by the presence of judges specialized in the commercial aspect. Furthermore, this commercial courts cannot meet that if they are competent qualitatively considering all commercial cases, and despite the judicial authority's interest in the commercial judiciary in Iraq. But, it was not at the required level ;it was limited to commercial lawsuits in which one of the parties is non-Iraqis. Also, the same procedures followed in the civil courts despite the specificity of commercial lawsuits that need a quick and complete judiciary. Thus, it is vital for the researcher to shed light on the specific jurisdiction of those courts through a study the commercial judiciary of the comparative countries (France, Egypt,and Saudi Arbia) and an attempt to benefit from their experiences and diagnose their negatives to advance the reality of commercial courts in Iraq.